Knowledge transfer for technology based interventions: Collaboration, development and evaluation. - Cudd, Peter A.; Mccullagh, P.J.; Mountain, G.A.; Black, N.D.; Nugent, C.D.; Zheng, H.; Davies, R.J.; Galway, L.; Hawley, M.S.; Mawson, S.J.; Wright, P.; Eccleston, C.; et al. (Technology & Disability, 2012)
The development of technology based interventions for healthcare requires collaborative working between multidisciplinary groups of scientists, engineers, designers, healthcare professionals, and of course end users. This necessitates transfer of knowledge between the various disciplines, preferably underpinned by defined methodologies. Exploitation and uptake of the technology requires participation of industry, typically a small to medium size enterprise (SME) or research department of a larger company and use of the technology requires flexibility of working and often change in healthcare practices. This paper documents the experiences of developing and evaluating two prototypes: the first for telerehabilitation of stroke and the second for self management of long term conditions (stroke, pain and coronary heart failure). We have identified two challenges: (a) knowledge transfer from domain specialists to engineers to facilitate technology development and (b) knowledge transfer back to the domain specialists to facilitate prototype evaluation and exploitation. The use of appropriate ICT tools and the incorporation of principles of human computer interaction have underpinned this approach. Users should influence the choice and functionality of the technology, but decisions must also be informed by technical considerations and possibilities for both hardware and software design. This is a two-way flow of information. How a prototype is taken forward into mainstream practice requires knowledge transfer from academia into the clinical and commercial sectors. Research funding enables both formative and summative prototype evaluation, but does not generally extend to examination of population based effectiveness, which is the evidence most often sought by health commissioners. Hence a process which provides the necessary underpinning for robust evaluation is proposed.